Studying the Organizational and Intra-Organizational Factors Affecting the Faculty Members' Organizational Silence in Islamic Azad University - Fahami, Manijeh; Mahmoudi, Mohammad Taghi; Shatalebi, Badri (Iranian Journal of Educational Sociology, 2022)
Purpose: This research was conducted with the aim of explaining the effect of organizational and intra- organizational factors affecting the faculty members' organizational silence in branches of Islamic Azad University. Methodology: The statistical population of this study was all faculty members of Islamic Azad University. The sample of this study was 380 ones according to the Cochran formula. After completing 380 questionnaires, analyzing the questionnaires was done using SPSS-23 software at the descriptive level of demographic characteristics including mean and standard deviation, minimum and maximum score of research variables and at inferential level using AMOS-23 software, multivariate analysis of variance and side findings by single-t and t-dependent tests. Findings: analysis of the results using SPSS-23 and AMOS-23 software showed that all factors of the organization had coefficients or impact factors higher than 0.3 at the level 0.001, and six dimensions related to the organizational factor and eight dimensions related to the intra-organizational factor, all affect the faculty members' organizational silence. Among the organizational dimensions, the human resources management and among the intra-organizational dimensions, the type of community culture had the highest impact on the organizational silence in Islamic Azad University. Two models with good fitting were presented for the organizational and intra-organizational factors. Discussion: All dimensions of human resource management, the characteristics of faculty members, the organization's characteristics, the organization culture, organizational climate, and organizational structure are effective in the organization factor. Human resource management has the most impact on silence and the organization type has the least impact on the silence